Model-assisted non-destructive testing - Wang, Guangyu (2018)
The reliability of non-destructive testing (NDT) is one of the important issues in ensuring the quality of structural components in different engineering fields. Among the several NDT methods, the eddy current is most desired method to inspect metallic parts looking for flaws and discontinuities. Eddy current testing is based on electrical current induction within a conductor by a changing magnetic field in the conductor due to Faraday's law of induction. The NDT methods are evaluated and characterized in a statistical manner by the probability of detection (POD) curve. However, this would require extensive physical experiments to collect sufficient data for obtaining a valid POD result. Hence, numerical models could be established for evaluating eddy current testing where data used in the POD study is obtained from simulation models. In this project, a simple and progressive Model Assisted Probability of Detection approach (MAPOD) is developed. MAPOD Evaluation and optimization of eddy current testing on Titanium alloy (Ti 6AL4V) will be discussed as well.